Epistemology and Social Theory: Internal and External Questions - Timothy Tambassi (Mutatis Mutandis: Revista Internacional de Filosofía)
The aim of this paper is to show how Rudolf Carnap’s distinction between internal and external questions might be extended and applied to social theory. Following Carnap, I argue that a question is internal to a framework if it can be answered within the given framework; on the other side, a question is external to a framework if it calls into question the framework itself. Here, I discuss this distinction and its consequences for the social theory through an analysis focused on the "Constitution of the Italian Republic" framework and on the notion of justice.